2018
DOI: 10.1152/ajpcell.00098.2018
|View full text |Cite
|
Sign up to set email alerts
|

The human ion channel TRPM2 modulates neuroblastoma cell survival and mitochondrial function through Pyk2, CREB, and MCU activation

Abstract: Transient receptor potential melastatin channel subfamily member 2 (TRPM2) has an essential function in cell survival and is highly expressed in many cancers. Inhibition of TRPM2 in neuroblastoma by depletion with CRISPR technology or expression of dominant negative TRPM2-S has been shown to significantly reduce cell viability. Here, the role of proline-rich tyrosine kinase 2 (Pyk2) in TRPM2 modulation of neuroblastoma viability was explored. In TRPM2-depleted cells, phosphorylation and expression of Pyk2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 86 publications
(151 reference statements)
4
59
0
Order By: Relevance
“…The TRPM2-S protein is of particular interest in that while short of channel-forming ability, it is capable of co-assembling with the full-length TRPM2 protein or channel and imposing dominant negative inhibition of the TRPM2 channel. Due to limited pharmacological tools for investigating the TRPM2 channel as discussed below, this dominant negative attribute of TRPM2-S has been employed in in vitro studies to interrogate the role of the TRPM2 channel in mediating ROS-induced Ca 2+ signalling and regulation of cellular functions by overexpression of TRPM2-S to suppress the formation or activity of functional channels by the endogenous full-length TRPM2 protein [ 33 , [74] , [75] , [76] , [77] ].…”
Section: Trpm2 Channel Properties Activation Mechanisms and Pharmacmentioning
confidence: 99%
“…The TRPM2-S protein is of particular interest in that while short of channel-forming ability, it is capable of co-assembling with the full-length TRPM2 protein or channel and imposing dominant negative inhibition of the TRPM2 channel. Due to limited pharmacological tools for investigating the TRPM2 channel as discussed below, this dominant negative attribute of TRPM2-S has been employed in in vitro studies to interrogate the role of the TRPM2 channel in mediating ROS-induced Ca 2+ signalling and regulation of cellular functions by overexpression of TRPM2-S to suppress the formation or activity of functional channels by the endogenous full-length TRPM2 protein [ 33 , [74] , [75] , [76] , [77] ].…”
Section: Trpm2 Channel Properties Activation Mechanisms and Pharmacmentioning
confidence: 99%
“…Human neuroblastoma SH-SY5Y cells have been widely used as a human neuronal cell model in the study of the molecular and signaling mechanisms for neurodegeneration, particularly those related to PD because of the catecholaminergic, albeit strictly speaking not dopaminergic, neuronal properties [31]. Studies from other groups and us have consistently documented functional expression of the TRPM2 channel in SH-SY5Y cells [21,23,24,32,33,34], but the findings regarding the role of the TRPM2 channel in SH-SY5Y cells are intriguing. A recent study using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay has shown that concentration-dependent reduction in cell viability after exposure to 10 to 400 µM H 2 O 2 or 125 to 500 µM MPP via inducing H 2 O 2 generation [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the data in cancer models mostly supports the conclusion that TRPM2 expression and function have an important role in preserving cancer cell viability and survival. Consistent with this view, the TRPM2 channel has been found to be highly expressed in numerous cancers including bladder, breast, head and neck, lung, pancreatic, prostate, melanoma, and neuroblastoma [ 51 ], among which most studies were focused on the neuroblastoma [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( Figure 2 ). The higher levels of ROS in cancer cells impel the enhancement of their anti-oxidant capacity to detoxify ROS and preserve cells viability.…”
Section: Transient Receptor Potential Melastatin 2 (Trpm2) Channelmentioning
confidence: 60%
“…Ca 2+ influx via TRPM2 results in the activation of phosphorylation of Pyk2, which regulates the cell survival and tumor growth of various cancers through the CREB pathway, leading to increased expression of phosphorylated and total CREB. When TRPM2 was inhibited, pPyk2, Pyk2, pCREB, and CREB were reduced and mitochondrial function as well as mitochondrial Ca 2+ uptake were impaired, together with more mitochondrial and cellular ROS, reducing cells survival and tumor growth [ 62 ]. Taken together, all studies in neuroblastoma show the critical role of TRPM2 that modulates both ROS production and the antioxidant response through the Ca 2+ entry via the channel activation.…”
Section: Transient Receptor Potential Melastatin 2 (Trpm2) Channelmentioning
confidence: 99%